Tipo de parideras y productividad de las cerdas y sus camadas en un sistema de producción porcina al aire libre - Echevarría, A. (2005)
Three farrowing facility types and two farrowing seasons were compared. The farrowing facility types were: FA: Open front farrowing accommodation with masonry walls and concrete floors; AR: Farrowing arc huts, in number of eight; UNRC: Improved farrowing huts. The followingvariables were registered: Piglets born alive (NLeNV); Piglets weaned (NLeD); Average (Kg.) weaning weight (PLeD); Number of piglets died between farrowing and weaning (NLeMN-D); Piglet?s mortality in percentage (%MLeN-D); Sows parities numbers (NOP). Feeding and management were similar for all treatments. Each sow and her litter were taken as a replication, which were accumulated over time, with sows of the same genetic origin assigned at random to each farrowing accommodation type. Farrowing season (EP) were: Autumn ? Winter (A-W) and Spring ? Summer (S ? S). The interaction Farrowing Facility Types x EP was not significative (p = 0,89). The %MLeN-D and NLeMN-D, were lower (p < 0,05) in the UNRC farrowing hut in relation to the FA facility. For %MLeN-D the results were 20,39 % ± 1,53 the FA facility vs. 15,76 ± 1,50 and 14,01 ± 1,73 % for the AR and UNRC farrowing huts, respectively. There were no differences (p > 0,05) between the two farrowing hut types. PLeD was bigger (p<0.05) for the UNRC farrowing hut, with no differences between AR and FA farrowing facility types. With regard to farrowing season (EP) the %MLeN-D was bigger (p = 0,024) during A ? W (20,68 % ± 1,57), compared with the S - S season (15,22 % ± 1,19).